(untitled) (Global Journal of Human-Social Science, 2020)
Generally Gold weights called mrammou in the Akan language are weights made of brass and used as a measuring system by the people of Akan in West Africa This was used for weighing gold dust which was the currency until that was replaced by paper money and coins These gold weights look like miniature models of everyday objects In the Akan society gold weights have played a significant part so far as the tradition and culture and the economy are concerned The gold weights have several cultural and symbolic undertones that require a study and an understanding by modern society Hence the study was conducted to revealed philosophical cultural and an outstanding value attached to the gold weights